2014
DOI: 10.1007/s00737-014-0426-7
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal depression case finding by community health workers in South Africa: feasibility of a mobile phone application

Abstract: Purpose Randomised controlled trials conducted in resource-limited settings have shown that once women with depressed mood are evaluated by specialists and referred for treatment, lay health workers can be trained to effectively administer psychological treatments. We sought to determine the extent to which community health workers could also be trained to conduct case finding using short and ultra-short screening instruments programmed into mobile phones. Methods Pregnant, Xhosa-speaking women were recruite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 68 publications
2
37
1
Order By: Relevance
“…Most of the articles ( n  = 18) were cross sectional prevalence studies and five ( n  = 5) were psychometric validation studies measuring reliability and validity of screening instruments. In reviewing these studies for reported psychometrics of sensitivity, specificity, Area under the curve and the relevant gold standards, two studies [32, 33] were excluded (no gold standard as defined by this study) and a further 23 studies were excluded due to inadequate reporting of psychometrics. One third of the articles ( n  = 11) reported psychometrics and a gold standard and met the final selection criteria for inclusion in the review (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the articles ( n  = 18) were cross sectional prevalence studies and five ( n  = 5) were psychometric validation studies measuring reliability and validity of screening instruments. In reviewing these studies for reported psychometrics of sensitivity, specificity, Area under the curve and the relevant gold standards, two studies [32, 33] were excluded (no gold standard as defined by this study) and a further 23 studies were excluded due to inadequate reporting of psychometrics. One third of the articles ( n  = 11) reported psychometrics and a gold standard and met the final selection criteria for inclusion in the review (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Shifting responsibility for mental health screening and/or treatment monitoring to non-specialist lay health workers is a priority area of research (89) that has been proposed as one potential mechanism for extending limited human resources (90). Such tasks will require brief, locally validated screening instruments (91, 92) whose use can be integrated cleanly into the lay health workers’ overall workflow without causing undue burden (26, 93). In many sub-Saharan African countries, mental health system resource constraints introduce additional concerns.…”
Section: Discussionmentioning
confidence: 99%
“…The EPDS measures the affective and cognitive symptoms that typically accompany depressive disorders (Kagee, Tsai, Lund, & Tomlinson, 2013). In this specific population of Xhosa-speaking pregnant and postpartum women, the EPDS has been shown to have a coherent internal structure (De Bruin, Swartz, Tomlinson, Cooper, & Molteno, 2004), high sensitivity and specificity for detecting major depressive disorder (Hung et al, 2014; Tsai et al, 2013; Tsai et al, 2014), and good construct validity (Dewing, Tomlinson, le Roux, Chopra, & Tsai, 2013; Hartley et al, 2011). Its internal consistency was confirmed in the baseline sample: the Cronbach’s alpha was 0.89, with a 95% confidence interval [CI] (computed using 500 bootstrap replications) of 0.88-0.90.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the pooled regression estimates provided information about the association between food insufficiency at one time point and depression symptom severity at the subsequent time point (e.g., food insufficiency at 6 months was correlated with depression symptom severity at 18 months). To aid in interpretation of the estimates and because caseness for (probable) depression is frequently of clinical interest, we defined probable depression as EPDS ≥13 (Hung et al, 2014; Rochat et al, 2006; Tsai et al, 2014) and re-fit a logistic regression model to the data. This model specified probable depression as the binary dependent variable and lagged food insufficiency as the explanatory variable of interest.…”
Section: Methodsmentioning
confidence: 99%